Variables cinéticas y stiffness vertical de bailarinas de ballet en la realización de un salto vertical. [Kinetic variables and vertical stiffness of female ballet dancers during a vertical jump]. - Daniel Rojano-Ortega (Ramón Cantó Alcaraz, 2021)
The aim of the current study was to analyze kinetic variables and vertical stiffness of young female ballet dancers during a vertical jump. 16 adolescent female Andalusian subjects volunteered to participate in this study. Eight were female ballet dancers (15.00 ± 1.07 years) following professional ballet classes and eight were sedentary female subjects (15.13 ± 1.36 years). They performed two types of vertical jumps, countermovement jump (CMJ) and countermovement jump with arm swing or Abalakov jump (ABK), and kinetic variables and vertical stiffness were analyzed. Results show that ballet dancers do not have an appropriate use of arm swings because the height of the jump increased only by 5.96% while the increase in sedentary subjects was of 22.25%. Significant differences in CMJ were found between both groups in jump height, average force, peak force, acceleration impulse, average power, peak power and normalized vertical stiffness (p < 0.01), as well as in length of the acceleration impulse and vertical stiffness (p < 0.05). These results show that female ballet dancers are more impulsive than female sedentary subjects. In addition, their high vertical stiffness value may indicate a good use of the stretch-shortening cycle and could be the cause or the effect of that impulsiveness. Future studies are required to compare female ballet dancers with other types of female athletes including vertical stiffness values.